Iron deficiency during pregnancy and lactation - Laura Wasserfallen; Diego Moretti (Current Opinion in Clinical Nutrition & Metabolic Care, 2026)
Purpose of review Iron deficiency persists as the most common nutritional deficiency worldwide and is highly prevalent among women of reproductive age. Pregnancy substantially raises iron requirements, increasing the risk of complications for mother and newborn particularly in low-income and middle-income countries. We summarize current evidence on the determinants, physiological adaptations, diagnostic thresholds, and management of iron deficiency during pregnancy and lactation, focusing on recent developments. Recent findings Maternal iron regulation during pregnancy involves progressive hepcidin suppression to enhance absorption and fetal iron transfer, though regulatory mechanisms remain incompletely understood. Daily supplementation may maintain maternal iron status more effectively than an alternate-day regimen but is associated with more side effects; thus, the choice of regimen should be individualized and based on context. Multiple micronutrient supplements offer superior clinical outcomes compared to iron-folic supplements. For moderate-to-severe iron deficiency or late-pregnancy correction, intravenous iron has proven to be well tolerated and highly effective. Summary Effective management requires early identification using ferritin-based diagnostic thresholds. Intravenous iron is an essential clinical tool for rapid correction or when oral iron is poorly tolerated. Sustainably improving maternal iron status globally would prevent iron deficiency in pregnancy but further necessitates integrated public health approaches – addressing dietary quality, low-dose supplementation, sanitation, and digital health interventions.